Molecular characterization and phylogenetic analysis of Fasciola hepatica from Peru. - Ichikawa-Seki, M. (2016)
The causative agent of fasciolosis in South America is thought to be Fasciola hepatica. In this study, Fasciola flukes from Peru were analyzed to investigate their genetic structure and phylogenetic relationships with those from other countries. Fasciola flukes were collected from the three definitive host species: cattle, sheep, and pigs. They were identified as F. hepatica because mature sperms were observed in their seminal vesicles, and also they displayed Fh type, which has an identical fragment pattern to F. hepatica in the nuclear internal transcribed spacer 1. Eight haplotypes were obtained from the mitochondrial NADH dehydrogenase subunit 1 (nad1) sequences of Peruvian F. hepatica; however, no special difference in genetic structure was observed between the three host species. Its extremely low genetic diversity suggests that the Peruvian population was introduced from other regions. Nad1 haplotypes identical to those of Peruvian F. hepatica were detected in China, Uruguay, Italy, Iran, and Australia. Our results indicate that F. hepatica rapidly expanded its range due to human migration. Future studies are required to elucidate dispersal route of F. hepatica from Europe, its probable origin, to other areas, including Peru.